Therapeutic strategies for congenital myasthenic syndromes - Lee, M; Beeson, D; Palace, J (Wiley, 2018)
To date, more than 25 genes have been implicated in the etiology of the congenital myasthenic syndromes (CMS), and an ever-growing phenotypic landscape is now encountered in the CMS clinic. Unlike the autoimmune form of myasthenia, there is no role for immunomodulatory agents in the treatment of CMS. The present-day drug repertoire comprises acetylcholinesterase inhibitors (mainly pyridostigmine), 3,4-diaminopyridine (3,4-DAP), ephedrine, salbutamol/albuterol, open-channel blockers (fluoxetine, quinidine), or a combination of these. These are prescribed by the specialist in an off-label manner, as there is no drug currently licensed for the treatment of these rare diseases. The effective pharmacological agent varies according to the genetic form of CMS, and it is important to realize that an agent that provides benefit in one CMS subtype can be harmful in another. In addition, the time to treatment response is variable and tends to be commensurate with the drug used. Here, we summarize for the clinician the therapeutic strategies employed in this ever-evolving disease spectrum. We also address the barriers to treatment and discuss the treatment of CMS in pregnancy.